China, the United States, and the future of Southeast Asia - Denoon, David (U.S.-China relations, 2017)
With China's emergence as a powerful entity in Southeast Asia, the region has become an unlikely site of conflict between two of the world's great powers. For anyone interested in understanding the evolving global balance of power, China, the United States, and the Future of Southeast Asia illuminates how countries as different as Thailand and Indonesia see the growing competition between Beijing and Washington.